2022
DOI: 10.3389/fsufs.2022.943309
|View full text |Cite
|
Sign up to set email alerts
|

Stability of crop pollinator occurrence is influenced by bee community composition

Abstract: Bees provide a vital ecosystem service to agriculture by contributing to the pollination of many leading global crops. Human wellbeing depends not only on the quantity of agricultural yields, but also on the stability and resilience of crop production. Yet a broad understanding of how the diversity and composition of pollinator communities may influence crop pollination service has previously been hindered by a scarcity of standardized data. We used outputs from Bayesian occupancy detection models to examine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…Some of the research is difficult to interpret because not all pollinators were assessed. Strawberry has fewer pollinators than other crops such as apple, bean and oilseed rape and a greater variation in total flower visits over time (Hutchinson et al, 2022). A study in The Netherlands demonstrated that insects visiting during the night were as important as those visiting during the day (Fijen et al, 2023).…”
Section: Number Of Achenes Per Fruitmentioning
confidence: 99%
“…Some of the research is difficult to interpret because not all pollinators were assessed. Strawberry has fewer pollinators than other crops such as apple, bean and oilseed rape and a greater variation in total flower visits over time (Hutchinson et al, 2022). A study in The Netherlands demonstrated that insects visiting during the night were as important as those visiting during the day (Fijen et al, 2023).…”
Section: Number Of Achenes Per Fruitmentioning
confidence: 99%